Geometric analysis of enhanced thermal conductivity in epoxy composites: A comparison of graphite and carbon nanofiber fillers. Issue 1 (5th September 2016) - Ruminski, Anne M.; Yang, Fan; Cho, Eun Seon; Silber, Joseph; Olivera, Edgar; Johnson, Thomas; Anderssen, Eric C.; Haber, Carl H.; Urban, Jeffrey J.
Abstract : We analyze the geometric effects of two different carbon fillers on the enhancement of the thermal conductivity of carbon‐epoxy composites. This study compares the thermal properties of composites containing graphite powder (2‐dimensional) and carbon nanofibers (1‐dimensional) incorporated in an industrial epoxy. Calculations using the generalized effective medium model were also used to examine the effect of the geometry and aspect ratio of the carbon filler. Experiments show that at a filler volume fraction loading of 0.10, the effective thermal conductivity of the composites was improved up to eightfold for carbon nanofiber and threefold for graphite in comparison to the neat epoxy. The superior performance of the carbon nanofiber composite is due to the larger aspect ratio of nanofiber which allows greater overlap between neighboring particles. However, this greater overlap also results in the composite becoming prohibitively viscous at low filler volume fractions. In graphite composite at the maximum filler volume fraction of 0.3, the resulting thermal conductivity improvement was 14‐fold over the neat epoxy. Calculations indicated that the improved thermal conductivity was primarily due to the filler particle geometry. Additionally, calculations suggest the wider distribution of graphite particle aspect ratio could have a positive influence on enhancing composite thermal conductivity.